The role of family relationships in migration decisions: a reconstruction based on implicit starting points in migrants’ justifications - Greco, Sara (Migration Letters, 2018)
This article integrates the discourse analytical approach of Argumentation theory in the study of international migration, with the aim to study the role of family relationships in migration decisions for international migrants. Argumentation theory studies dialogical exchanges in which participants give reasons to justify their standpoints. In this perspective, interviews with migrants are considered as dialogical exchanges, in which migrants provide accounts of their crucial migration decisions by giving justificatory reasons. By reconstructing these reasons, implicit starting points emerge, in particular endoxa, i.e. participants’ personal values and beliefs that are at the basis of their decisions. The reconstruction of implicit endoxa allows a nuanced access to the role of family relationships within migrants’ accounts of their decisions.